Household food waste: attitudes, barriers and motivations - Baboo, Shabanaz; Bhadain, Meetali; Nunkoo, Robin (Emerald, 2021)
Purpose – Food waste at the household level represents a major component of all food waste. Therefore minimizing food waste at the household level remains an important component of the food chain responsibility. This study explores the problem of food waste in Mauritius through an understanding of households’ attitudes toward food waste and their motivations and barriers to food waste recycling. Design/methodology/approach – The study uses a grounded theory approach to identify thematic categories that represent participants’ attitudes toward food waste and the barriers they face to food waste reduction. We used a purposive sampling technique to guide the selection of participants. Interviews were conducted with 14 participants: three experts in food waste and 11 households. The data were analyzed using the tools of grounded theory. Findings – Participants’ expressed views on food waste included (1) guilt toward wasting food; (2) (lack of) environmental awareness; (3) financial considerations and (4) exemption from responsibility. The findings also led to the development of four themes that defined the barriers participants face to recycling food waste: (1) lack of awareness; (2) space limitations on recycling methods; (3) inadequate policy and (4) lack of time/priority. Practical implications – Addressing the problem of food waste requires a holistic approach that takes into account households’ attitudes to food waste, their motivation and barriers to food waste recycling as well as the regulatory and institutional framework governing food waste management in Mauritius. Policymakers should try to improve households’ knowledge about food waste through educational campaigns. The authorities can provide different types of bins to households freely to facilitate the sorting out of waste and impose a fee for food waste generated beyond a certain limit or provide subsidies to them for handling food waste properly. Originality/value – The management of food waste is particularly challenging for small islands developing states because of their unique characteristics of smallness, limited resources and environmental vulnerability. Appropriate interventions to reduce household food waste require place-based and geographically sensitive analyses that take into account the specificities of local food and waste management systems and cultural norms with respect to food. However, there is not only a paucity of research on household food waste, but most studies have been carried out in nonisland economies. The study contributes to the limited research on household food waste in small islands.